Barriers to timely disclosure of HIV serostatus: A qualitative study at care and treatment centers in Dar es Salaam, Tanzania. - Neelam Ismail (Public Library of Science (PLoS), 2021)
Introduction Disclosure of Human Immunodeficiency Virus (HIV) status is important to prevent the spread of HIV and maintain the health of people living with HIV, their spouses, and the community. Despite the benefits of disclosure, many people living with HIV delay disclosing their status to those close to them thereby increasing the risk for disease transmission. This study aimed to determine the barriers to timely disclosure of HIV serostatus for people living with HIV in Dar es Salaam, Tanzania, and identify what motivated disclosure. Methods A qualitative descriptive study using in-depth individual interviews was conducted with10 participants attending HIV care and treatment centers in Dar es Salaam. The participants were people living with HIV who had delayed disclosing their serostatus for more than one month after diagnosis. Data was analyzed using qualitative content analysis. Results Three categories emerged from the analysis: Barriers hindering timely disclosure, motivation for disclosure of serostatus, and consequences of delayed disclosure. Barriers to timely disclosure included denial of one's status, the fear of stigmatization, fear of being separated or divorced, the need to protect loved ones, and lack of adequate knowledge about the disease. Reasons that motivated disclosure included gaining social support, preventing disease transmission and wanting to be at peace. Conclusion Timely disclosure is hindered by stigma because HIV is negatively perceived by the public. People living with HIV prefer not to disclose to avoid the negative consequences of disclosure, especially because of fear of being discriminated against and losing their social status, which plays a major role in social status in Tanzania. Trust and adequate counseling from health care workers helps prompt disclosure.